2017
DOI: 10.1016/j.neubiorev.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurocognitive aspects of hallucinations in Alzheimer’s disease

Abstract: Due to their prevalence, hallucinations are considered as one of the most frequent psychotic symptom in Alzheimer’s disease (AD). These psychotic manifestations reduce patients’ well-being, increase the burden of caregivers, contribute to early institutionalization, and are found to be related with the course of cognitive decline in AD. Considering their consequences, we provide a comprehensive account of the current state of knowledge about the prevalence and characteristics of hallucinations in AD. We provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 100 publications
1
40
1
1
Order By: Relevance
“…1 , Supplementary Tables 1ab ). Their presence has been repeatedly associated with more severe cognitive and functional decline, earlier institutionalization, higher burden of disease, and increased mortality [4] . It is therefore essential to better understand hallucinations in AD.…”
Section: Introductionmentioning
confidence: 99%
“…1 , Supplementary Tables 1ab ). Their presence has been repeatedly associated with more severe cognitive and functional decline, earlier institutionalization, higher burden of disease, and increased mortality [4] . It is therefore essential to better understand hallucinations in AD.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher discovered that individuals with AD have higher odds of auditory disturbances. This finding, to my knowledge, is novel and this is the first study that has reported auditory disturbances as being predictive of AD, excluding auditory hallucinations, which are considered to be frequent psychotic symptoms of AD (25). There could be biological plausibility that could be investigated with a larger sample, as the result is of borderline significance due to small sample size.…”
Section: Discussionmentioning
confidence: 64%
“…[1][2][3] More than half of patients with AD will experience psychosis during their illness. [4][5][6] Hallucinations and delusions are frequently distressing to the individual and their caregivers and are associated with worse disease outcomes relative to AD patients without psychosis, 4 including accelerated cognitive decline, 7,8 more rapid progression of functional impairment, 9 increased hospital admissions, 10 earlier admission to institutional care, 8,9 and increased mortality. 9,11 In addition, psychotic symptoms are often antecedent to or comorbid with other neuropsychiatric symptoms like agitation, aggression, and depression, further adding to the impact on the individual and others making Alzheimer's disease psychosis (ADP) more difficult to treat.…”
Section: Introductionmentioning
confidence: 99%